Soil respiration in relation to photosynthesis of Quercus mongolica trees at elevated CO2. - Yumei Zhou (PLoS ONE, 2010)
Knowledge of soil respiration and photosynthesis under elevated CO(2) is crucial for exactly understanding and predicting the carbon balance in forest ecosystems in a rapid CO(2)-enriched world. Quercus mongolica Fischer ex Ledebour seedlings were planted in open-top chambers exposed to elevated CO(2) (EC = 500 µmol mol(-1)) and ambient CO(2) (AC = 370 µmol mol(-1)) from 2005 to 2008. Daily, seasonal and inter-annual variations in soil respiration and photosynthetic assimilation were measured during 2007 and 2008 growing seasons. EC significantly stimulated the daytime soil respiration by 24.5% (322.4 at EC vs. 259.0 mg CO(2) m(-2) hr(-1) at AC) in 2007 and 21.0% (281.2 at EC vs. 232.6 mg CO(2) m(-2) hr(-1) at AC) in 2008, and increased the daytime CO(2) assimilation by 28.8% (624.1 at EC vs. 484.6 mg CO(2) m(-2) hr(-1) at AC) across the two growing seasons. The temporal variation in soil respiration was positively correlated with the aboveground photosynthesis, soil temperature, and soil water content at both EC and AC. EC did not affect the temperature sensitivity of soil respiration. The increased daytime soil respiration at EC resulted mainly from the increased aboveground photosynthesis. The present study indicates that increases in CO(2) fixation of plants in a CO(2)-rich world will rapidly return to the atmosphere by increased soil respiration.